2017
DOI: 10.1080/09638288.2017.1305456
|View full text |Cite
|
Sign up to set email alerts
|

The effects of multimodal rehabilitation on pain-related sickness absence – an observational study

Abstract: When implemented nationwide, multimodal rehabilitation appears not to reduce sickness absence compared to treatment-as-usual. Implications for Rehabilitation A nationwide implementation of multimodal rehabilitation was not effective in reducing sickness absence compared to treatment-as-usual for persons with nonspecific musculoskeletal pain. Multimodal rehabilitation was effective in reducing the risk of future disability pension for persons with nonspecific musculoskeletal pain compared to treatment-as-usual.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 37 publications
8
18
0
1
Order By: Relevance
“…The rehabilitation programme interventions for chronic pain are unique in the sense that the participants themselves play a crucial role in the rehabilitation process and participation in the MMR interventions as an active team member. The findings of improvements in emotional function, pain intensity and activity in daily life in this study confirm the generally positive results found in previous studies of MMR (9,(26)(27)(28)(29).…”
Section: Discussionsupporting
confidence: 92%
“…The rehabilitation programme interventions for chronic pain are unique in the sense that the participants themselves play a crucial role in the rehabilitation process and participation in the MMR interventions as an active team member. The findings of improvements in emotional function, pain intensity and activity in daily life in this study confirm the generally positive results found in previous studies of MMR (9,(26)(27)(28)(29).…”
Section: Discussionsupporting
confidence: 92%
“…Since MMRP was initiated as a new rehabilitation intervention, healthcare professionals from the primary healthcare units reported both negative and positive aspects when implementing it (33). They also experienced similar difficulties in managing work ability and return to work in MMRP, as reported from other primary care units in Sweden (37). At the time of the present data collection, the MMRPs did not contain specific work-directed interventions, which have been found to be an important factor for return to work (38).…”
Section: Discussionmentioning
confidence: 90%
“…Two recently published papers concerning the effects of MMRP on pain-related sickness absence in Sweden and within the rehabilitation warranty presented differing results. Busch et al [60] compared participants of MMRPs with matched controls and found that MMRPs were not effective in reducing sickness absence compared with care as usual. MMRP was, nevertheless, effective in reducing the risk of future disability pension.…”
Section: Discussionmentioning
confidence: 99%
“…There are a few notable differences between these two studies and our study. Busch et al [60] included patients at two different time periods at both specialist and primary healthcare from the last quarter of 2009 until the end of 2010 and retrieved data from the Swedish Social Insurance Agency. Rivano Fischer et al [51] included data from specialist care reported to the SQRP during 2007-2011 supplemented with sickness absence data from the Swedish Social Insurance Agency.…”
Section: Discussionmentioning
confidence: 99%